Effects of Social Context on Consensus and Majority Vote Decision Making - Tjosvold, Dean; Field, Richard (Academy of Management Journal, 1983)
A laboratory study of group decision making found that social context (competitive or cooperative) and decision strategy (consensus or majority voting) affected decision acceptance, understanding, decision time, and affective reactions to the group, although decision quality was not affected.